The effect of integrated reporting quality on cost of capital: A comparison between developed countries and developing countries - Chen, Xingyi (2022)
Due to frequent corporate scandals, corporate disclosure evolved another new form, integrated reporting. Since integrated reporting was introduced, it attracted much attention in the field of academy. Some studies have investigated integrated reporting and cost of capital. But only a few papers assessed the quality of integrated reporting, and no research did the comparison between different countries. Thus, this paper intends to examine the effect of integrated reporting quality on cost of capital and investigate whether such effect show differences in developed countries and developing countries. The results prove that integrated reporting quality has negative relationship with cost of capital; Such a relationship is more significant in developing countries than developed countries. Therefore, the enhancement of integrated reporting quality is an innovative measure to decline cost of capital. And this measure is more applicable to developing countries.